The human flavoproteome - Lienhart, Wolf-Dieter (Academic Press, 2013)
Vitamin B(2) (riboflavin) is an essential dietary compound used for the enzymatic biosynthesis of FMN and FAD. The human genome contains 90 genes encoding for flavin-dependent proteins, six for riboflavin uptake and transformation into the active coenzymes FMN and FAD as well as two for the reduction to the dihydroflavin form. Flavoproteins utilize either FMN (16%) or FAD (84%) while five human flavoenzymes have a requirement for both FMN and FAD. The majority of flavin-dependent enzymes catalyze oxidation–reduction processes in primary metabolic pathways such as the citric acid cycle, β-oxidation and degradation of amino acids. Ten flavoproteins occur as isozymes and assume special functions in the human organism. Two thirds of flavin-dependent proteins are associated with disorders caused by allelic variants affecting protein function. Flavin-dependent proteins also play an important role in the biosynthesis of other essential cofactors and hormones such as coenzyme A, coenzyme Q, heme, pyridoxal 5′-phosphate, steroids and thyroxine. Moreover, they are important for the regulation of folate metabolites by using tetrahydrofolate as cosubstrate in choline degradation, reduction of N-5.10-methylenetetrahydrofolate to N-5-methyltetrahydrofolate and maintenance of the catalytically competent form of methionine synthase. These flavoenzymes are discussed in detail to highlight their role in health and disease.